Morphology modulation of silica mesoporous nano- and microparticles for atrazine - controlled release - Fookes, Federico Adrian (2022)
Atrazine is a moderately toxic triazine, used as a selective pre- and post-emergence herbicide. After application, it remains in the environment due to its low biodegradability causing severe environmental effects. Several controlled release systems have been proposed in order to minimize the negative impact of the herbicide on the environment. In particular, mesoporous silica nanoparticles have shown great potential in the agricultural area due to their controlled size and porosity, high surface area and non-toxicity. In this work, silica nano- and microparticles were synthesized and evaluated as atrazine delivery systems. The morphology and size distribution of the particles were characterized using dynamic light scattering (DLS) and scanning electron microscopy (SEM). The release profiles were studied by in vitro assays in water. In addition, phytotoxicity tests were performed using Lactuca sativa seeds. The mesoporous nano- and microparticles exhibited sustained release for at least 24 h and reduced phytotoxicity compared to free atrazine.